AGENDA MANAJEMEN UTANG LUAR NEGERI INDONESIA PASCA PEMILU 2009 - Yumitro, Gonda (Jurnal Bestari, 2009)
Indonesia has a big problem related to owning debts. Every year, the number of the debts  always increase because the country development. Besides, a way to solve the crisis still depends on the debts. Indonesia does not have independency to build its economic system based on people of  interest. So, there is no real development in Indonesia because it prefers to have growth than justice. The development is the catching up fallacy. Moreover, in the presidential election of 2009, we hope that we can find the leader who want to bring out Indonesia from this "debt  trap".